Endoscopic vs Open Treatment of Laryngotracheal Stenosis. (23rd August 2013) - Khosla, Sid; Rutter, Michael J.; de Alarcon, Alessandro; Sandhu, Guri; Halum, Stacey L.; Hillel, Alexander T.
Abstract : Program Description: A significant challenge in the surgical management of laryngotracheal stenosis is when to choose an open repair over an endoscopic approach. This clinical decision‐making process is made more difficult by the fact that there is significant controversy about this topic, and thus there is no general consensus. This miniseminar will focus on the surgical details of different endoscopic and open procedures. On the panel, there will be both surgeons who favor endoscopic approaches and those who frequently do both. Discussion will be further enhanced by the use of multiple case presentations and interactive audience participation. Educational Objectives: 1) Recite the details of multiple endoscopic approaches, including the use of balloons, lasers, stents, application of mitomycin C, and injection of steroids for both children and adults. 2) Describe how co‐morbidities, patient age, patient preferences, airway surgical history, and nature (eg, length, location, firmness) modify the decision of when to choose an open versus endoscopic approach. 3) Recognize when to choose a cricotracheal resection versus a laryngotracheal resection and the details of both procedures.